2021
DOI: 10.3390/ijms22115687
|View full text |Cite
|
Sign up to set email alerts
|

The Multifaceted Nature of Nucleobindin-2 in Carcinogenesis

Abstract: Nucb2 is a multifunctional protein associated with a variety of biological processes. Multiple studies have revealed that Nucb2, and its derivative nesfatin-1, are involved in carcinogenesis. Interestingly, the role of Nucb2/nesfatin-1 in tumorigenesis seems to be dual—both pro-metastatic and anti-metastatic. The implication of Nucb2/nesfatin-1 in carcinogenesis seems to be tissue dependent. Herein, we review the role of Nucb2/nesfatin-1 in both carcinogenesis and the apoptosis process, and we also highlight t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 101 publications
0
6
0
Order By: Relevance
“…In recent years, the potential link between NUCB2/ nesfatin-1 and tumorigenesis has been progressively revealed [11]. NUCB2/nesfatin-1 contributes to the development and progression of various cancers, such as prostate, colon, and breast cancers [30][31][32], and the underlying mechanism may be related to its ability to promote cell proliferation, migration, and invasion [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the potential link between NUCB2/ nesfatin-1 and tumorigenesis has been progressively revealed [11]. NUCB2/nesfatin-1 contributes to the development and progression of various cancers, such as prostate, colon, and breast cancers [30][31][32], and the underlying mechanism may be related to its ability to promote cell proliferation, migration, and invasion [33].…”
Section: Discussionmentioning
confidence: 99%
“…NUCB2/nesfatin-1 has been reported to promote cell proliferation, migration, and invasion in various cancers, including breast, colon, prostate, endometrial, thyroid, and bladder cancers [10]. Moreover, high expression of NUCB2/nesfatin-1 is associated with key traits of cancer as well as poor prognoses and outcomes [11]. Mechanistically, it has been shown that NUCB2/nesfatin-1 improved the migration, invasion, and EMT characteristics of colon and renal cancer cells through stimulation of the AMPK/TOC1/ZEB1 pathway [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Reinforcement 7 was applied throughout the analysis. The use of a higher reinforcements (e.g., [16][17][18], would allow the identification and quantification of nesfatin-1 at concentrations that would allow its determination directly in human fluids, e.g. plasma, serum, liquid cerebrospinal.…”
Section: Calculation Of Relative Standard Deviation Values (Rsd) and ...mentioning
confidence: 99%
“…Nucleobindin-2/Nesfatin-1 is also a component of various secreted body fluids, including saliva, synovial fluid, milk, and plasma or serum [15,16]. Therefore, there is a nowadays need to define new prognostic and predictive markers to make treatment options more personalized [6,17].…”
Section: Introductionmentioning
confidence: 99%
“…Nucleobindin 2 (NUCB2) is a precursor protein of nesfatin-1, which was ordinally identi ed in hypothalamic nuclei and associated with food intake and energy homeostasis [7,8]. The protein has characteristic functional domains such as a Leu/Ile rich region, two Ca 2+ binding EF-hand domains separated by an acidic amino acid-rich region, and a leucine zipper [9]. The role of NUCB2 in tumor development and metastasis is Janus-like.…”
Section: Introductionmentioning
confidence: 99%